„W jaki sposób zredukować szkodliwą emisję gazów cieplarnianych na terenie Łodzi o 55% do 2030 roku?” –II Łódzki Panel Obywatelski w praktyce (Public participation in urban climate policy making: The example of Lodz, 2024)
In the last few years, two citizens’ assemblies have been held in Lodz, focusing on the mitigation and adaptation of the city to climate change, and consequently, improving the quality of life for the residents of Lodz. The first panel addressed greenery in the city, while the second focused on finding answers to the question, “How to reduce harmful greenhouse gas emissions in Lodz by 55% by 2030?”. This chapter highlights the key conditions and determinants of the implementation of the 2nd Lodz Citizens’ Assembly, from the planning stage through execution to completion. As a result, the chapter should provide practical knowledge and inspiration for city leaders and authorities to conduct social participation processes using citizens’ assemblies as a tool of urban policy.